Assinatura de microRNAs circulantes (hsa-let-7e-5p, hsa-miR-106a-5p, hsa-miR-28-3p e hsa-miR-542-5p) como promissores biomarcadores para o diagnóstico precoce de câncer colorretal - Silva, Camila Meirelles de Souza (2019)
Colorectal cancer is a disease with high incidence and mortality and represents one of the great challenges for public health. It is high mortality rate is, in part, related to the diagnosis of advanced disease. This has encouraged the search for new tools for early detection of colorectal cancer that are more effective, less invasive and that can be performed on a large scale. Under this perspective, the analysis of the serum expression of MicroRNAs (miRNAs) is presented as an alternative, since they are highly stable in the blood and are frequently altered in several pathologies, especially in cancer. The miRNAs are a class of small RNAs that act as transcriptional regulators affecting several pathophysiological processes including the developmental stages of colorectal cancer. In this context, the present study was conducted to identify a differential expression profile of circulating miRNAs as a possible noninvasive method for early diagnosis of colorectal cancer. For this, we used the methodology of large scale analysis to identify the expression profile of plasma miRNAs in subjects carefully divided into non-cancerous group (healthy volunteers, patients with hyperplastic polyp and adenoma) vs. cancer group (colorectal cancer and colorectal cancer with metastasis). Subsequently the differentially expressed miRNAs were validated by qRT-PCR. The discriminant power of the miRNAs between the groups was evaluated by ROC curve and multivariate model and the prediction of targets and pathways involved was analyzed using the bioinformatics tools. Were identified four miRNAs (hsa-let-7e-5p, hsa-miR-106a-5p, hsa-miR-28-3p and hsa-miR-542-5p) overexpressed in the cancer group when compared to non-cancer group, being the hsa-miR-28-3p the strongest diagnostic marker (ROC 0.7841 [0.6890-0.8873]) followed by hsa-miR-542-5p (ROC 0.7174 [0.6167-0.8181]). Association between two miRNAs also showed high discriminant power between groups cancer vs. non-cancer with the following associations: hsa-miR-28-3p and hsa-miR-542-5p (ROC 0.7363 [0.6670-0.8056]); hsa-miR-28-3p and hsa-miR-106a-5p (0.7324 [0.6597-0.8051]) and (hsa-miR-28-3p and hsa-let-7e-5p (ROC 0.7264 [0.6555-0.7974]), and association of three and four miRNAs: hsa-miR-106a-5p, hsa-let-7e-5p and hsa-miR-28-3p (ROC 0.7102 [0.6506-0.7676]) and hsa-miR-106a-5p, hsa-let-7e-5p, hsa-miR-28-3p and hsa-miR-542-5p (ROC 0.7053 [0.6543-0.7564]). Additionally, the prediction of targets and signaling pathways in silico showed that hsa-let-7e-5p, hsa-miR-106a-5p, and hsa-miR-28-3p regulate enriched genes in pathways associated with cancer. Therefore, In the present study it was demonstrated that the evaluation of serum expression of hsa-let-7e-5p, hsa-miR-106a-5p, hsa-miR-28-3p and hsa-miR-542-5p can be used as a miRNAs signature for the less-invasive and early diagnostic of colorectal cancer.